Optimalisasi manuver valsalva untuk mengurangi nyeri telinga akibat perubahan tekanan udara - Fitri Anggraeni; Luluk Eka Meylawati; Suroso Suroso; Ridho Fidrajaya (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Rapid changes in air pressure can create a pressure imbalance between the middle ear cavity and the external environment, often resulting in ear pain, a sensation of fullness, ringing in the ears (tinnitus), temporary hearing impairment, and other forms of discomfort. This condition, known as ear barotrauma, occurs due to environmental pressure changes such as during aircraft takeoff or landing, diving activities, or while inside pressurized environments like hyperbaric chambers. The Valsalva maneuver is a method used to alleviate this issue; it involves closing the nose and mouth and attempting to exhale, thereby increasing air pressure within the nasal cavity and Eustachian tubes. Purpose: To optimize the Valsalva maneuver technique as a non-invasive intervention for reducing ear pain caused by air pressure changes in patients undergoing hyperbaric chamber therapy. Method: This activity consisted of interactive education and practical training conducted at the Hyperbaric Unit of Dr. Mintohardjo Naval Hospital (RSAL). The target audience comprised patients at high risk of developing ear pain (ear barotrauma) due to air pressure fluctuations during hyperbaric therapy. Twenty-eight patients participated in the activity. Respondents' knowledge and understanding were assessed using a